Infantile hemangiomatosis: An unusual cause of infantile congestive heart failure - Aamir Rashid; Zubair Mushtaq Tramboo; Javed Iqbal Bhat; Hilal Rather (Heart India)
We report a rare case of congestive heart failure (HF) in a 2-month-old female with multiple cutaneous and hepatic hemangiomas. A thorough clinical examination and comprehensive imaging lead to early diagnosis. Early treatment with systemic corticosteroids and propranolol led to notable clinical improvement and hemangioma regression. This case emphasizes the importance of considering infantile hemangiomatosis in the differential diagnosis of infant HF and highlights the efficacy of prompt, multidisciplinary intervention.